A comparative study of observed and estimated values of evaporation in India - SARMA, V. V. (MAUSAM, 1973)
The evaporation losses for water yield studies are being estimated by extrapolation from evaporation charts based on Rowher's empirical formulae. Since these charts were prepared using the old meteorological normals these have been revived using the latest 1960 normals of 216 stations. These values are compared with evaporation charts based on observed pan evaporimeter losses at 80 stations. Monthly and annual charts showing the anomalies between the observed and empirically estimated Rowher's values are presented and the significant features described with an explanation of the anomalies, A comparison of spot values of evaporation by both these methods has also been made and results discussed.